(untitled) (TAJ: Journal of Teachers Association, 2009)
Brain abscess may be solitary or multiple. They appear as areas of ill-defined cerebritis to mature well defined focal suppurative lesion with capsulated abscesses. Multiple brain abscess recognized in as many as 50% of patients. In this study 30 patients were analyzed. Solitary brain abscess were more than multiple abscess. Age ranges from 6 years to 35 years. Male to female ratio was 5:1. Intra parenchymal brain abscess occurred in all cases (100%), subdural or extradural lesions were nil. Brain abscesses were associated with CSOM. CT scan done in all (100%) patients as diagnostic tools. All (100%) patients under went Burr-hole evacuation with broad-spectrum antibiotic therapy and 2 patients (06.66%) treated with long term anti tubercular therapy. V-P shunt was made in 1 patient (03.33%) who had persistent venriculomegaly. In this study mortality rate was zero. doi: 10.3329/taj.v16i2.3887 TAJ December 2003; Vol.16(2): 73-75